First soviet occupation and genocide in Lithuania in 1940-1941: occupation experience and lithuanian history concept problems - Vyšniauskas, Arūnas (Genocidas ir rezistencija, 2005)
This text is an attempt to find new ways to immortalise the experience of occupation in the light of the changed geopolitical situation following Lithuania’s accession to the European Union and NATO. It also addresses the issues of interpretation of the events of 1940–1941 in history textbooks, which, according to the Lithuanian media debate in 2005, has stirred considerable interest in society.